A Mídia e as Apropriações do Patrimônio Vivo Pernambucano no Contexto do Ativismo Folkmidiático - Barreto, Lucy Regina Farias de Melo Miranda Costa (2010)
The Law of Registration of the Patrimônio Vivo Pernambucano can be identified as an instrument of the State which aims to record and protect producers of the popular culture of Pernambuco, bringing in the context of media activism, we identify the occurrence of an institutionalization and why not say, a nationalization of the popular activities representative for the state. That‟s why the state is also contributing to the folkmedia activism. The state gives support to the folk media activists, already registered, be able to act in their communication networks. As well as representatives of their origin groups, the Patrimônio Vivo become a representation of the identity and culture of Pernambuco. Of course we know that by recognizing these groups and people as producers and disseminators icons of the popular culture in Pernambuco, the state somehow projects a little of its cultural identity and, having no doubts, the media, in particular the one being part of this study, the newspaper Jornal do Comercio and the website pe360graus, they are means of communication that make the range and the reach of this projection become even greater. This study aims to understand how the mediation process regarding the living heritage, the state, the society and the media, all these aspects seen from the perspective of the media activism made by those living heritage.